Understanding the Needs of the Young Employees in the City of Joy - Mukerje, Nayan Ranjan; Rawat, Lachhman Singh (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
India is a young nation with almost 27.2% of the population below the age of 29 years. The City of Joy has a thriving ITES sector. These individuals have aspirations, these aspirations drive their actions. The educated youth employed today will be the business leaders of tomorrow. If the current employers are not fulfilling their aspirations, the young employees attrite. Substituting the talent is time consuming and expensive. Attrition leads to loss of knowledge – brain drain, which negatively impacts business. The talented young employees if retained locally, will help to develop the region and in-turn India. ITES sector is one of the biggest employers of Generation Z youths in Kolkata. My study aims to identify, analyse and understand the factors that are in demand amongst the members of this talent pool. A structured questionnaire utilising Likert scale was used to collect data from the target population – employees of the ITES sector aged between 21 – 25 years. The research design adopted to study the raw data was descriptive approach. Quantitative techniques like Principal Component Analysis, Kaiser-Meyer-Olkin Measure of Sampling Adequacy and Varimax with Kaiser Normalization were used for detailed analysis of the data. The findings of the research will help HRs to design proper retention initiatives and organisational policies to retain the talent pool in the region and such retentions will eventually contribute in developing the entire region by making it attractive destination for investors and business firms.